Colocation as network: Types and performance implications of structural positions in colocation network - Kim, Minyoung; Oh, Chang Hoon; Han, Jukyeong (Journal of International Business Studies, 2024)
This study investigates types and performance implications of competitive colocation from a network perspective. Drawing on the literature of industrial organization, economic geography, and social network analysis, we introduce a new conceptualization of location choice and colocation as an inter-firm network relationship and advance a theoretical framework on the dimensions of competitive colocations and their implications on firm performance. We maintain that this new approach provides an integrative framework to better understand the types and performance implications of competitive colocation. We first introduce two distinct dimensions of a focal firm’s competitive colocation, intensity and diversity, along with which we develop a typology of a focal firm’s structural position in the competitive colocation network: simple colocation, multicountry colocation, and multifirm colocation. We test predictions of the theoretical framework with subsidiary location information of the firms listed in the Fortune Global 500. The results of empirical analyses corroborate the main thesis of the current study that the intensity and diversity of a focal firm’s competitive colocation individually and jointly influence firm performance. In addition, we find that, on average, multicountry colocation outperforms the other two types of colocation.